(untitled) (Comprehensive Journal of Science, 2025)
This study aims to evaluate exposure to crystalline silica in the cement industry and to analyze its health effects on workers, while applying the Six Sigma methodology to improve occupational safety and reduce exposure to this hazardous substance. The paper focuses on identifying sources of exposure, assessing associated health risks, and proposing a practical framework to minimize exposure using Six Sigma. A mixed-methods approach was adopted, including a literature review, a case study, and both quantitative and qualitative data analysis. The findings aim to provide practical recommendations for enhancing worker safety in the cement industr